Reduced order modelling for an air-conditioned room via gappy proper orthogonal decomposition - Chen, Xiao Jing (2017)
This study aims to obtain an optimal airflow of a ventilated room. A good air-conditioning system is needed to maintain or improve the thermal comfort for the inside occupant. Computational Fluid Dynamics (CFD) is able to simulate the expected flows in the room. This study uses ANSYS Fluent software to carry out two-dimensional and three-dimensional ventilation simulations and analyze the airflow patterns in the room. Many cases are simulated with varying parameters, including inlet air velocity, location of inlet and outlet vents and presence of the occupant. A rectangular block with a constant temperature of 310K is molded to represent an occupant. Steady-state and transient-state contours of static temperature and velocity magnitude are attained from simulations. And then these contours are analyzed to observe the effects of various parameters on thermal comfort. After discussion, it is concluded that the configuration with one inlet and one outlet positioned on the same side performs the best for thermal comfort. And the inlet air velocity of 2m/s which is 45°/135° from the inlet is the most suitable, as far as thermal comfort is concerned. This study enhances the understanding of interactions of various parameters, benefits and limitations of two-dimensional and three-dimensional simulations, and the importance of transient-state analyses. The findings of this study can be applied to real-life situations.